Pengaruh Customer Experience dan E-WOM terhadap Revisit Intention melalui Brand Awareness sebagai Mediator pada Hotel Bintang 5 di Surabaya - Heryanto, Elizabeth Florenza; Lewi, Gabriella Josephine; Wijaya, Verina (Jurnal Ilmiah Pariwisata, 2025)
Technological developments drive competition in the hotel industry to provide the best service to increase guest repeat visits. Memorable experiences and positive word-of-mouth through social media marketing play a role in building awareness and reconsideration of a hotel brand. Surabaya, a business and tourism center, becomes a focus of research, especially 5-star hotels with high brands and service quality standards. This study explores application of customer experience and e-WOM to increase guests’ revisit intention. Seeing the research gap, brand awareness which plays an important role in the eyes of guests becomes a mediator in the implementation of customer experience and e-WOM on revisit intention. A quantitative approach with PLS-SEM technique, Smart PLS device, and purposive sampling techniques were applied for research process. The sample obtained was 180 respondents from specified population, namely 5-star hotel guests in Surabaya. Results of the study revealed that customer experience and e-WOM have a positive effect on revisit intention through brand awareness. The research is expected to offer valuable insights for hoteliers in improving competitiveness in the hospitality sector as well as further research opportunities for academics. Keywords: customer experience, E-WOM, brand awareness, revisit intention, Surabaya